Characterization of Novel Germplasm for Yield and Yield Related Traits in Finger Millet (Eleusine coracana L. Gaertn) - Mohit Sharma,; K. Madhusudan,; Prashant Vasisth,; Parul Gupta, (Annals of Agricultural Research, 2023)
Genetic enhancement of any crop depends on the selection which will be effective if variability is existing in that crop species for different characters. In this regard, an investigation was performed to comprehend the genetic variability for seed yield and its related attributes traits in finger millet. A novel set of 148 germplasm accessions procured from IIMR, Hyderabad comprising were sown during kharif 2019 at Zonal Agriculture Research Station (ZRC), V. C. Farm, Mandya in Randomized Complete Block Design (RCBD) with two replications. Significance of MSS for traits under investigation depicted presence of adequate variation and substantiates the worthiness of experimental material used in the study. Narrow difference between PCV and GCV showed less influence of environment on expression of attributes under investigation. High heritability in conjunction with high GAM were registered for seed yield plant per plant, 1000 seed weight, fingers per ear, finger length, earhead length and productive tillers per plant stipulated indicating the predominance of additive gene action. Seed yield plant per plant was significantly and positively correlated with straw yield per plot, days to 50% flowering, days to maturity, 1000 seed weight, finger length, peduncle length, plant height, and productive tillers per plant. The findings revealed that accessions 5158, 6772, 2899, 4516, 6493, 5425, 5337, 6563, 5160, 6526, 5736, 5200, 5412, 6423 and 3376 were promising based on superiority over check varieties and can be used for the strengthening of the seed yield in future breeding programmes.